The kinetic of point defect transformation during the annealing process in electron-irradiated silicon - Gaidar, G.P.; Dolgolenko, A.P.; Litovchenko, P.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The A-centers (VO) annealing and transformation of precursors to form stable СiОi defects during these processes are described. It was found the necessity to take into account annihilation of vacancy type defects with the interstitial type mobile defects to describe the annealing of defects. It was shown that the energies of migration for vacancy (V) and interstitial carbon atoms Сi that are defined by the degree of their localization in silicon lattice at the temperature close to 550 K are equal Emv = 1.1 eV and Emc = 1.16 eV, accordingly.